From welfare to workfare: a modernização da hegemonia capitalista - análise da assistência social na Suíça - Wehrle, Beat (2011)
The following dissertation investigated the welfare states as a specific configuration of social security systems developed in industrialized countries during the twentieth century. This model, known as welfare, recognizes social rights in a wide format and transforms the political nature of the relations between the State and the society. The objective of this study was the analysis of a supposed transition from the welfare state to a welfare production state known as workfare, as a decentered regulation of the welfare production and as a centered regulation on the insertion of its users on the labor market. The investigative process had as objective the analysis of the thesis of this transition as a modernization process of the capitalist hegemony having as the specific focus the social assistance in Switzerland. The investigation, of qualitative character, was substantiated methodologically in bibliographic material, in testimonials of the actors of the social assistance in Switzerland, obtained by structured interviews, as in the participative observation of the researcher. The accomplished study verified that the reconfiguration of welfare in workfare perspective does not get processed necessarily by the dismounting of the welfare systems. Nevertheless, it changes the regulation of the welfare production transforming the social assistance in a social control apparatus serving the globalized capitalism